Impact of Aerosols (Saharan Dust and Mixed) on the East Mediterranean Oligotrophic Ecosystem; Results from Experimental Studies - Barak Herut (Frontiers Research Topics, 2017)
In oligotrophic environments, dust and nutrient inputs via atmospheric routes are considered important sources of macro-nutrients and micro-trace metals fuelling primary and secondary production. Yet, the impact of these dust inputs on the microbial populations is not fully investigated in the Eastern Mediterranean Sea (EMS). The response of oligotrophic systems to dust inputs, whether as positive or negative feedbacks to autotrophic and heterotrophic production and thus to biogeochemical cycling, is important to examine further. Experimental studies have explored nutrient additions in various combinations to determine the limiting resource to productivity or N2 fixation. Recent experimental studies have applied dust enrichments to bottle or mesocosm incubations of seawater from different oceanic regions. This research topic presents two Eastern Mediterranean dust addition mesocosm experiments using, for the first time, real aerosol additions, pure Saharan dust and mixed aerosols (a natural mixture of desert dust and polluted European particles), as well as other EMS aerosol experimental studies. The Topic includes manuscripts introducing results on: a) the impact of Saharan dust vs mixed aerosols on the autotrophic and heterotrophic surface microbial populations in the EMS, b) the impact of single vs multi-pulses of Saharan dust introduction into the pelagic environment of the EMS and c) other experimental studies of aerosol impacts on the EMS ecosystem.